MicroRNA-18a-5p regulates hepatic lipid accumulation in response to high-fat diet - Petito, Giuseppe; Magnacca, Nunzia; Cuomo, Arianna; Ventriglia, Maria; Fusco, Angelo; Venditti, Massimo; Falvo, Sara; Potenza, Nicoletta; Lanni, Antonia; Cioffi, Federica; Senese, Rosalba (Frontiers in Physiology, 2025)
IntroductionMetabolic Dysfunction-Associated Steatotic Liver Disease (MASLD), formerly known as Nonalcoholic Fatty Liver Disease (NAFLD), is characterized by hepatic lipid accumulation, inflammation, and progressive liver injury, potentially leading to steatohepatitis, cirrhosis, and hepatocellular carcinoma (HCC). Central to MASLD pathogenesis are dysregulated lipid metabolism and unresolved endoplasmic reticulum (ER) stress, with sterol regulatory element-binding protein 1 c (SREBP1c) and the protein kinase RNA-like ER kinase (PERK) -eukaryotic initiation factor 2 alpha (eIF2α) signaling pathway playing key roles. This study investigates the regulatory role of microRNA-18a-5p (miR-18a-5p) in lipid accumulation during MASLD induced by a high-fat diet (HFD).MethodsExperiments were performed on male Wistar rats fed either a standard or high-fat diet to induce MASLD. In addition, HepG2 cells were treated with fatty acids to establish an in vitro model of MASLD.ResultsIn HFD fed rats, miR-18a-5p was significantly downregulated, coinciding with increased SREBP1c expression, PERK pathway activation, hepatic lipid accumulation, apoptosis, and impaired autophagy flux. A similar pattern was observed in fatty acid-treated HepG2 cells, confirming the translational relevance of the findings. Notably, miR-18a-5p overexpression reduced lipid accumulation, attenuated ER stress, restored autophagy, and suppressed apoptosis, in both in vivo and in vitro models.ConclusionThese results identify miR-18a-5p as a key regulator of lipid homeostasis and ER stress in MASLD, suggesting its potential as a novel therapeutic target. Understanding such molecular mechanisms is crucial for developing effective strategies against this increasingly prevalent liver disease.